Attitude of General Population Towards People with Physical Disability - Hisam, Aliya; Mashhadi, Syed Fawad; Fatima, Zainab; Chohan, Remesha; Malhi, Orooba; Abdullah, Muhammad; Asif, Muttahar; Abbasi, Abdullah (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To find out the attitude of the general population towards disabled individuals. Study Design: Cross-sectional study design. Place and Duration of Study: Rawalpindi/Islamabad, from Nov 2021 to Apr 2022. Methodology: The attitude towards physical disability was assessed by including 2 separate standardised scales and was divided into 3 parts; i) the Demographics, ii) the ATDP scale, and iii) CDP scale. The data was collected through google forms because of the pandemic. The sample size was 166. The data analysis was performed on SPSS 25.0. Result: Out of 166(100%) participants in the study, 137(82.5%) lived in urban areas and the mean age was 22 years. Out of which 38(22.9%) participants reported to have higher education. People from various professions participated in the research. The CDP scale showed 104(62.7%) participants had low contact, 45(27.5%) had no contact and 17(10.2%) had a high contact. The mean ATDP score was 72.12% showing a positive attitude overall. The attitude was not significantly associated with contact (p-0.405), education (p-0.342), gender (p-0.870), income (p-0.605), and presence of doctor in the family (p-0.893). Conclusion: This research concluded that the attitude towards the disabled of the general population of twin cities was positive.Contact, presence of doctors within the family and demographic factors; income, education, and gender had no association in determining the attitude of the general population towards the disabled. Thus, inferring that our education and doctors are not making enough of a difference and moral education should be further stressed upon.